Globalization, Gluts, Innovation or Irrationality : What Explains the Easy Financing of the U.S. Current Account Deficit? - Balakrishnan, Ravi (IMF Working Papers; Working Paper ;, 2007)
This paper examines the roles of U.S. financial innovation, financial globalization, and the savings glut hypothesis in explaining the rise in U.S. external debt, first in a portfolio balance model, and then empirically. Perhaps surprisingly, financial deepening and falling home bias in industrialized countries explain a large share of external financing. The savings glut hypothesis (including difficult-to-track petrodollar recycling) and U.S. financial innovation are also important, in part as a cause of declining home bias in industrialized countries. The latter underscores the importance of not looking at these factors in isolation, but rather as a constellation of forces that can be self-reinforcing.